2019
DOI: 10.1116/1.5111727
|View full text |Cite
|
Sign up to set email alerts
|

Growth of pulsed laser deposited few-layer WS2 films

Abstract: X-ray photoelectron, Raman, and diffraction studies of few-layered pulsed laser deposited WS 2 films were performed as a function of laser fluence and frequency to understand the impact on structure and properties. Supersaturation of the growth surface created by high fluence was conducive to nucleation and growth, but the obtained films were sulfur deficient. Sulfur desorption at high fluence is due to large kinetic energy transfer and energetic peening of the growing film from the impinging flux. Loss of sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…By sufficiently lowering laser fluence, S/W ratio improved from 1.1 to 1.8 which improved mobility from 0.1 to 6.5 cm 2 Vs −1 [54]. Annealing in a sulfur rich environment served to improve mobility further to 19.5 cm 2 Vs −1 [54]. This shows the crucial role proper stoichiometry plays in material quality.…”
Section: Pulsed Laser Deposition (Pld)mentioning
confidence: 88%
See 4 more Smart Citations
“…By sufficiently lowering laser fluence, S/W ratio improved from 1.1 to 1.8 which improved mobility from 0.1 to 6.5 cm 2 Vs −1 [54]. Annealing in a sulfur rich environment served to improve mobility further to 19.5 cm 2 Vs −1 [54]. This shows the crucial role proper stoichiometry plays in material quality.…”
Section: Pulsed Laser Deposition (Pld)mentioning
confidence: 88%
“…They observed that film quality improved significantly upon annealing in a sulfur rich environment, suggesting that sulfur vacancies are also a challenge for monolayer WS 2 [53]. Rathod et al [54] further explored the consequences of stoichiometry, growing centimeter-scale monolayer films on Si/SiO 2 under various laser fluences. Increasing laser fluence tended to decrease sulfur in the final product [54].…”
Section: Pulsed Laser Deposition (Pld)mentioning
confidence: 99%
See 3 more Smart Citations